The Relationship between Family Support and Patient Anxiety when Undergoing Rapid Screening Tests COVID-19 in Hospitals - Putri, Prestasianita (Nursing and Health Sciences Journal (NHSJ), 2024)
The Covid-19 pandemic has made hospital screening more stringent. All patients undergo an antigen swab examination, and this examination can cause anxiety for the patient and family. This study aims to identify family support for the anxiety of patients undergoing Rapid Tests while in hospital. The independent variable in this study is family support, while the dependent variable is the anxiety of patients undergoing rapid COVID-19 screening tests. This study had 154 respondents using an accidental sampling technique. This research design uses a correlation type with a cross-sectional approach. Bivariate statistical tests use Kendall's Tau. The results of this study were that respondents had good family support of 71.4%, the anxiety of patients undergoing the COVID-19 rapid test screening was mild anxiety of 50.6%, and there was a relationship between family support and the anxiety of patients undergoing the COVID-19 rapid test screening in Hospital with p-value = 0.000 (p<0.05). Family support has a positive impact in reducing patient anxiety when undergoing a rapid COVID-19 screening test. Therefore, interventions involving the family in the patient care process can be considered a strategy to improve the patient's psychological well-being. Further studies are recommended to explore specific mechanisms by which family support may influence patient anxiety in other medical contexts. Keywords: Covid-19, Family Support, Anxiety, Rapid Test